Numerical мodeling of magnetized plasma compressed by the laser beams and plasma jets - Kuzenov, V.V.; Ryzhkov, S.V. (Вопросы атомной науки и техники, 2013)
Magneto-inertial fusion (MIF) including magnetized target compression by high energy laser pulses is fastgrowing area of research. Distinctive feature of this problem is presence of initial seed fields (the imposed external pulse magnetic field) and compression of a magnetic flux by laser beams (laser driver) and plasma jets (plasma liner). High-convergence uniform implosion and properly synchronized laser beams (laser intensity > 10²⁰ W/m²) are considered. Influence of external magnetic field on driver-fuel target interaction is discussed. Preliminary test results of magnetized plasma target compression by high energy laser pulses are shown. It can be argued that the magnetic field in terms of vortices plays a stabilizing role, which is manifested in the fact that the vortex structures dissipate in the presence of an externally applied magnetic field. Магнитно-инерциальный термоядерный синтез, включая сжатие замагниченной мишени мощными лазерами – быстро развивающаяся область науки. Отличительная особенность данной задачи – наличие начального затравочного поля (наложенного внешнего импульсного магнитного поля) и сжатие магнитного потока лазерными пучками (лазерный драйвер) или плазменными струями (плазменный лайнер). Рассмотрен случай однородного и синхронного лазерного облучения (интенсивность излучения > 10²⁰ Вт/м²). Представлены результаты выполненных тестовых расчетов для стационарных струй плазмы с учетом магнитного поля. Можно утверждать, что магнитное поле, с точки зрения вихрей, играет стабилизирующую роль, которая проявляется в том, что вихревые структуры диссипируют при наличии магнитного поля. Магнітно-інерціальний термоядерний синтез, включаючи стиснення замагніченої мішені потужними лазерами, галузь науки, яка швидко розвивається. Відмітна особливість даної задачі – наявність початкового запалювального поля (накладеного зовнішнього імпульсного магнітного поля) і стиснення магнітного потоку лазерними пучками (лазерний драйвер) або плазмовими струменями (плазмовий лайнер). Розглянуто випадок однорідного і синхронного лазерного опромінення (інтенсивність випромінювання > 10²⁰ Вт/м²). Представлені результати виконаних тестових розрахунків для стаціонарних струменів плазми з урахуванням магнітного поля. Можна стверджувати, що магнітне поле з точки зору вихорів грає стабілізуючу роль, яка проявляється в тому, що вихрові структури дисипірують при наявності магнітного поля.